FEDEX@HASDEU & CHINDII PROFESIONALE – PLEDOARIE PENTRU INOVAREA ACTIVITĂȚII: CONFERINȚĂ PUBLICĂ - KULIKOVSKI, Conf. univ., director, Departamentul studii și cercetări, Lidia (BIBLIOPOLIS, 2020)
The libraries need rethinking the concept and the perception of changes in relation with the society and vis-à-vis to their future. The future of the libraries is not connected with books, activities – not only with them. The future library will become a platform, hub, incubator, community center, innovative environment for community learning… at the head will be the culture of services, projects… The Municipal Library efforts in order to identify the path, methods, forms for future activities have been discussed and have been tested in the „Chindii profesionale”, Zilele FedEx@Hasdeu. The paper is about the impact of these activities and is correlated with future actions in consolidation of the ways to the ML future.